Diseño de una ODN para una red GPON en la localidad de Loja-Noroccidente, Corporación Nacional de Telecomunicaciones CNT E.P - Albuja Narváez, José Alberto (2014)
In this document the process of designing an ODN FTTH access network using GPON technology, which allows providing converged services (voice, Internet and television) regardless of the infrastructure is detailed, and thus can meet the demand of telecommunications services that users require in the northwest sector of the city of Loja, because it is a highly commercial and residential area. To enable the design of GPON ODN for study and information gathering was held for the defined area (Figure 1.1), existing and potential users, identifying potential service users requiring total demand and demand telecommunications. He then proceeded to conduct a technical design for GPON ODN network using the current regulations of the CNT E.P. regarding technical standard technical drawing and design standard. Moreover it was a financial cost-benefit analysis to determine the viability of the project.